2018
DOI: 10.1002/slct.201801092
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Reduction of α, β‐Unsaturated Aldehydes and Ketones under Ambient Conditions using Tetraalkylphosphonium‐based Ionic Liquids

Abstract: An efficient and green protocol for highly selective reduction of α,β-unsaturated aldehydes and ketones at room temperature is described in a range of ionic liquids, in the absence of noble metal catalysts, by using NaBH 4 as reducing agent. Most notably, using [P 6,6,6,14 ][N(CN) 2 ] ionic liquid, in absence of organic solvent, within 10 min, 97% conversion of cinnamalde-hyde was achieved with 100% selectivity towards cinnamyl alcohol. The ionic liquid was easily recycled without any noticeable decline in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, to address global environmental sustainability issues, green chemical processes must be developed, and the most straightforward way is to conduct it without using any solvent. Even though green solvents like water, , ionic liquids, , and supercritical CO 2 , have been reported, a solvent-free reaction system for CAL hydrogenation has not been reported to date. This challenge prompted us to design a catalyst using a method that immobilizes the solvent on a support, where the solvent can be easily recovered and reused.…”
Section: Introductionmentioning
confidence: 99%
“…However, to address global environmental sustainability issues, green chemical processes must be developed, and the most straightforward way is to conduct it without using any solvent. Even though green solvents like water, , ionic liquids, , and supercritical CO 2 , have been reported, a solvent-free reaction system for CAL hydrogenation has not been reported to date. This challenge prompted us to design a catalyst using a method that immobilizes the solvent on a support, where the solvent can be easily recovered and reused.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids have shown promising catalytic activities, , and provide an attractive alternative to solid acids with benefits such as good thermal stability, ease of handling, and good recyclability . SO 3 H functionalized ionic liquids have been investigated by Li et al and Liu et al Liu et al found [(HSO 3 -p) 2 im]­[HSO 4 ] to be the most active catalyst, exhibiting 95% conversion of glycerol and selectivity to di and triacetin of 51.4 and 5.5%, respectively, after 30 min at 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The selective hydrogenation of α, β ‐unsaturated aldehydes and ketones is a useful functional group transformation in organic synthesis and is of high importance in the fine chemical industry especially in the production of pharmaceuticals, fragrances and flavours [39] . As we have mentioned previously especially in the case of nucleophilic hydride reagents and because of the steric and electronic reasons, generally aldehydes are more susceptible to reduction than ketones.…”
Section: Catalytic Activitymentioning
confidence: 99%